2012
DOI: 10.1016/j.jff.2011.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Eicosapentaenoic and docosahexaenoic acids as inflammation-modulating and lipid homeostasis influencing nutraceuticals: A review

Abstract: PPAR SREBP Cholesterol Functional foods A B S T R A C T The present review summarizes the underlying biochemical and molecular mechanisms that can explain cardioprotective effects of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) and their competition with arachidonic acid as a substrate of cyclooxygenase COX-2 and lipoxygenase 5-LOX, and modulation of the signaling pathways of the transcription factors peroxisome proliferator-activated receptor (PPAR), sterol-response element binding protein (SREB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 107 publications
1
59
0
1
Order By: Relevance
“…However, recently several researchers have challenged it on the basis of outcomes of epidemiological and clinical studies, and concluded that linoleic acid (LA: ω-6) was not involved in reduction of CHD, and may possibly increase it (Ramsden et al 2010;Komprda 2012) due to production of 2-and 4-series prostaglandins and prostacyclin compounds. Indeed several risk factors such as physical inactivity, suboptimal diet, smoking, stress and increased use of alcohol are attributable to chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…However, recently several researchers have challenged it on the basis of outcomes of epidemiological and clinical studies, and concluded that linoleic acid (LA: ω-6) was not involved in reduction of CHD, and may possibly increase it (Ramsden et al 2010;Komprda 2012) due to production of 2-and 4-series prostaglandins and prostacyclin compounds. Indeed several risk factors such as physical inactivity, suboptimal diet, smoking, stress and increased use of alcohol are attributable to chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in these lipid profiles are related to the development of metabolic syndromes such as diabetes and atherosclerosis 4 6 . n-3HUFA intake also has a significant effect on inflammation 7 . As a result, fish gather significant attention as healthy food; many kinds of foods and a medicine containing n-3HUFAs are available on the market and are applied practically.…”
Section: Introductionmentioning
confidence: 99%
“…ALA is a limiting factor in dietary omega-3 consumption because it must be converted to EPA and DHA to meet the body's demand for omega-3 fatty acids. As this conversion of ALA to EPA and DHA is not an efficient process, it is imperative that EPA and DHA be consumed via dietary sources [11,12]. Dietary sources of EPA and DHA are very limited to specific food items, which leads to low dietary consumption depending on the geographical region and dietary preferences.…”
Section: Methodsmentioning
confidence: 99%
“…Even if one meets the ALA recommendation, the body must undergo the inefficient conversion process to EPA and DHA. In a population where seafood is a staple, it is imperative to consider EPA and DHA recommendations, which currently are not established [11,21].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation